A National View of Transition Planning Participation and Post-School Goals for English Learners with Disabilities. Issue 1 (1st January 2023) - Wu, Yi-Chen; Thurlow, Martha; Johnson, David
ABSTRACT: The increase in English learners (ELs) with disabilities has been reported by others, yet little is known about the transition planning meeting experiences of this population and their post-school expectations. This study explored transition planning experiences and post-school expectations of a nationally representative sample of ELs with disabilities by examining the National Longitudinal Transition Study 2012 dataset. Results showed that ELs with disabilities were more likely to take a passive role in transition planning and less likely to be involved in developing goals during the Individualized Education Program (IEP) transition planning meeting. ELs with disabilities, compared to non-ELs with disabilities, had lower expectations for being financially independent by age 30. These findings underscore the importance of specifically addressing the cultural and linguistic needs of ELs with disabilities during the IEP transition planning process and suggest recommendations for educational policy and practice for this population.